2001
DOI: 10.1562/0031-8655(2001)073<0532:piletr>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Phototesting in Lupus Erythematosus Tumidus—Review of 60 Patients¶

Abstract: Photosensitivity is an important characteristic feature of several forms of lupus erythematosus (LE), and induction of skin lesions by UV-A and UV-B irradiation has been proved to be an optimal model for evaluating light sensitivity in patients with this disease. Because lupus erythematosus tumidus (LET) has rarely been documented in the literature and is often difficult to differentiate from other photodermatoses such as polymorphous light eruption, we performed photoprovocation tests in 60 patients with LET … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
1
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(36 citation statements)
references
References 43 publications
3
31
1
1
Order By: Relevance
“…This is unlike the results of other studies, which generally reported a higher photosensitivity of patients with SCLE 7,[9][10][11][12][13][14][15][16] and also with the recently described subset of LET. 27 All the patients in our study who reacted to visible light also had a reaction to UVR, either UVA and ⁄ or UVB. Ten patients showed no response to UVA but were provoked by UVB and six patients reacted to UVA but not to UVB.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This is unlike the results of other studies, which generally reported a higher photosensitivity of patients with SCLE 7,[9][10][11][12][13][14][15][16] and also with the recently described subset of LET. 27 All the patients in our study who reacted to visible light also had a reaction to UVR, either UVA and ⁄ or UVB. Ten patients showed no response to UVA but were provoked by UVB and six patients reacted to UVA but not to UVB.…”
Section: Discussionmentioning
confidence: 92%
“…Another photosensitive subset of LE, LE tumidus (LET), was described recently, with 72% of the patients reacting to UV photoprovocation. 27 These different rates of photosensitivity in patients with the various subtypes of LE may indicate variation in underlying pathophysiological processes in LE, although at the moment no evidence exists for this and further investigation is required. There was no significant difference in photosensitivity among the subtypes of LE in our study.…”
Section: Discussionmentioning
confidence: 99%
“…A phototest study performed in 60 patients with LET revealed characteristic skin lesions in 72% of cases. 11 Around 50% of cases reacted to UV-A, 50% reacted to UV-B, and 63% reacted to combined UV-A and UV-B. In some cases, specific skin lesions in these phototests appeared up to 4 weeks after the last irradiation.…”
Section: Discussionmentioning
confidence: 95%
“…Photosensitivity studies in LET have revealed that 50% of cases are induced by UV-B radiation. 11,12 • We described a case with initial findings of reticular erythematous mucinosis, without epidermal changes, that developed criteria for SLE. A repeated biopsy performed in the same area revealed the epidermal changes of lupus erythematosus.…”
Section: Discussionmentioning
confidence: 99%
“…UV irradiation was performed in accordance with an established phototesting protocol. 7 The minimal erythema dose (MED) for broadband UVB (Fig. 1a) and broadband UVA ( Fig.…”
Section: Reportmentioning
confidence: 99%